The Effect of School Culture on Student Achievement in Restructured High Schools - Thomas, Holley (Valdosta State University, 2011)
No Child Left Behind (NCLB) mandates that if a school fails to make Adequate Yearly Progress (AYP) for a fifth consecutive year, the school district must initiate plans to fundamentally restructure the school. Proactive school districts with failing high schools have started restructuring schools into smaller schools in an effort to improve achievement in high schools. Current literature discusses high school restructuring and student achievement as well as the organization of restructured schools, but does not address the culture in restructured high schools and how it affects student achievement. The purpose of this study was to identify specific aspects of school culture that correlate with high and low achieving restructured high schools as perceived by the teachers working in those schools. This study found that there are differences in the cultures of high and low achieving restructured high schools. This study also found that schools that performed better on the English Language Arts portion of the Georgia High School Graduation Test also had higher scores on specific culture themes such as Concern for the school and stakeholders and Intent and direction. Schools that performed worse on the English Language Arts portion of the Georgia High School Graduation Test had low scores in the Empowerment theme.
Keywords: No Child Left Behind; High School; Graduation Test; English Language Arts; Adequate Yearly Progress; School environment--United States; Educational change; Education--Standards--United States